Extending the theory of planned behavior to explain the role of awareness in accepting Islamic health insurance (takaful) by microenterprises in northwestern Nigeria. Issue 4 (8th July 2019) - Kazaure, Mansur Ahmed
Abstract : Purpose: Nigeria is a country with very low health insurance coverage, with only 3 per cent of its population in the public and private sector covered by conventional health insurance. This made it possible for the exploration of alternative methods of insurance in Muslim dominated northwestern Nigeria. Thus, this paper aims to extend the theory of planned behavior to understand the role of awareness in the acceptance of Islamic health insurance ( takaful ) among microenterprises in northwestern Nigeria. Design/methodology/approach: The methodology used was a purely quantitative survey with data collected from seven states that form the northwestern Nigeria. Findings: The findings revealed that attitude, social influence and perceived behavioral control have a significant direct influence on takaful acceptance intention among microenterprises in northwestern Nigeria, while awareness does not. It was also discovered that awareness of takaful moderates the influences of social influence and perceived behavioral control on takaful acceptance intention, but it failed to moderate the influence of attitude on takaful acceptance intention in the same context. Research limitations/implications: The implication is that despite the acceptance intention more awareness is required to enlarge the takaful market in the region. The study contributes to the theories of reasoned action and planned behavior through the integration of awareness as a moderator. Originality/value: The work is pioneering, extent literature in the area of takaful failed in investigating the role of awareness as a moderating variables in Nigeria where much awareness of the concept is desirable.